Psychological distress and associated factors among medical students in Addis Ababa, Ethiopia: A cross-sectional study (May 2018) - Light Tsegay; Getinet Ayano (Journal of Affective Disorders Reports, 2024)
Background: Psychological distress, posing a substantial threat to the well-being of medical students, is linked to heightened risks of academic struggles and suicidal tendencies. Despite its profound impact, comprehensive studies on the prevalence and determinants of psychological distress among medical students remain scarce, particularly in developing nations like Ethiopia. This study sought to robustly assess the prevalence of psychological distress and its determinants among medical students in Addis Ababa, Ethiopia. Methods: A rigorous institution-based cross-sectional study involving 423 medical students utilized a stratified random sampling technique. The Kessler Psychological Distress Scale (K10) served as the assessment for psychological distress. The scale has been validated for use in Ethiopia and demonstrates a sensitivity of 84.2 % and specificity of 77.8 %. Scores above 20 on the K10 were considered as indicative of psychological distress, while scores falling within the ranges of 10–19 were likely to indicate wellness. Logistic regression was used to investigate the association between dependent and independent variables. Odds ratios (OR) with corresponding 95 % confidence intervals (95 % CI) were meticulously calculated to discern the strength of associations. Results: Out of the 423 participants, 390 were included in the current study, resulting in a response rate of 92.2 %. A formidable prevalence of psychological distress was exposed, registering at 42.82 % (95 % CI 37.97, 47.82 %). Strikingly, female students exhibited a disproportionately higher prevalence (62.03 %) compared to their male counterparts (37.93 %). Factors such as test anxiety, suicidal attempts, and suboptimal time management were pivotal contributors to escalated rates of psychological distress. Multivariable analysis underscored the significance of certain determinants, revealing that high GPA scores were protective [AOR 0.25, 95 % CI 0.13, 0.49], while inadequate social support [AOR 5.7, 95 % CI 2.96, 11.24], a history of suicidal attempts [AOR 5.62, 95 % CI 1.34, 23.4], and problematic test anxiety [AOR 5.02, 95 % CI 2.67, 9.42] were associated with heightened vulnerability. Conclusion: This study unveils a pervasive and concerning landscape of psychological distress among medical students in Addis Ababa, with a stark gender disparity. Interventions targeting test anxiety, fortifying social support structures, and providing accessible mental health resources are essential to mitigate these challenges and enhance the resilience and well-being of medical students, thereby reducing or preventing psychological distress.